Aplikasi Limbah Cair Pabrik Kelapa Sawit dan NPK Phonska terhadap Pembibitan Kelapa Sawit (Elaeis guineensis Jacq.) di Main Nursery - Setiawan, Yoga; Elfis, Elfis (Jurnal Agroteknologi, Agribisnis, dan Akuakultur, 2026)
This research aims to determine the interaction and main effects of Palm Oil Factory Liquid Waste and Phonska NPK on the growth of oil palm seedlings in the main nursery, and was carried out at the Experimental Garden of the Faculty of Agriculture, Islamic University of Riau, started from April 2023 to July 2023. This research uses a Completely Randomized Factorial Design consisting of two factors. The first factor is the concentration of palm oil mill liquid waste (C) consisting of 4 levels, namely: 0; 0.75; 1.5; 2.25 liters per polybag and the second factor is the NPK Phonska (N) dose consisting of 4 levels, namely: 0; 25; 50; 75 g per polybag. The parameters observed were increase in plant height, increase in number of leaf midribs, increase in length of leaf midrib, increase in tuber diameter, increase in longest root length and root volume. The data was analyzed statistically and continued with the HSD test at the 5% level. The results of the study showed that the effect of the interaction of palm oil factory liquid waste fertilizer and NPK phonska was not significantly different on the parameters of increasing frond length, increasing stem diameter, root volume and longest root length. The best treatment dose for palm oil mill liquid waste is 2.25 liters per polybag and NPK Phonska 75 g per polybag. The main influence of palm oil mill liquid waste is significant on all observation parameters. The best treatment is a dose of 2.25 liters per polybag. The main effect of NPK Phonska is significant on all observation parameters. The best treatment is at a dose of 75 g per polybag.